Open Educational Resources for Blended Learning in High Schools: Overcoming Impediments in Developing Countries - Larson, Richard C.; Murray, M. Elizabeth (Journal of Asynchronous Learning Networks, 2008)
With today's computer and telecommunications technologies, every young person can have a quality education regardless of his or her place of birth. This is the dream that Open Educational Resources (OERs), when viewed as a right rather than a privilege, are directed to realize. For developing countries, we propose a type of OER initiative that leverages not only technology but also the skills of the in-class teacher, that utilizes not only the Internet but also lower-tech delivery platforms, and that is created not only by developed countries of the West but also by educators in many countries worldwide. We outline the design of a cross-border, collaborative learning and teaching system called the Blended Learning Open Source Science or Math Studies Initiative (BLOSSOMS), with an associated partnership network established for its implementation in developing countries. BLOSSOMS is to develop a large, free repository of blended-learning video modules for high school math and science classes, created by gifted volunteer educators from around the world and designed to offer potentially transformative learning exercises that will enhance critical thinking skills and retain students' interest in math and science. The initiative has been designed and developed within a multinational network of partner organizations in the developing world, a characteristic that distinguishes it from many other OER projects.
Keywords: Asynchronous Communication; Barriers; Blended Learning; Cooperative Programs; Developing Nations; Educational Resources; Educational Technology; High Schools; Instructional Innovation; Learning Modules; Program Development; Shared Resources and Services; Social Networks; Video Technology; ⛔ No DOI found